DEVELOPING TEACHING LEARNING FOR INTEGRATED MANAGEMENT OF CHILDHOOD ILLNESS (IMCI): A QUALITATIVE STUDY IN ACEH INDONESIA - Wirda Hayati; Sri Supar Yati Soenarto; Fitri Haryanti; Yayi Suryo Prabandari (Belitung Raya Foundation, Indonesia, 2017)
Background: Integrated Management of Childhood Illness (IMCI) is an integrated guideline in dealing with infants and sick children at the community health center. However, many students cannot apply this guideline because they are not being exposed. Objective: This study aims to explore the perspectives of nurse educators and clinical instructors regarding the effectiveness of teaching learning process of IMCI in diploma nursing students. Methods: This was a qualitative study with interpretive approach. There were nine informants selected using purposive sampling, which consisted of nurse educators and clinical instructors. Data collection was conducted in December 2016 - February 2017 using focus group discussions and in-depth interviews. Data were analyzed using Colaizzi process. Result: There were four themes emerged from data, namely 1) Competency of IMCI for Diploma Nursing Students, 2) Deepening of IMCI Material, 3) Learning methods of IMCI in the class and clinic should be active and structured, 4) Student confidence in the application of IMCI in clinical setting. Conclusion: The learning process of IMCI will have an impact on the improvement of knowledge, skills and attitude in the application of IMCI in the clinical setting.